Steric And Eustatik Effect Contributions To Sea Level Change Based On Altimetry Satellite Argo And Grace Satellite Data Within 1992-2012 Period (The Study Area: The Western Pacific Ocean) - Prayudha Hartanto; Sella Lestari Nurmaulia; Kosasih Prijatna (Indonesian Journal of Geospatial, 2013)
Abstract. The change of sea level in the western Pasific Ocean is one of the biggest change in the world. This is caused by steric and eustatic factors. In the period of 1992-2012, the total change of sea level in this area based on the Topex/Poseidon satellite data, Jason 1 and Jason 2, was 6. 982 ± 3.493 mm/year. Based on the temperature and salinity from Argo floats for the period 2000